Нелінійна математична модель електрохімічного конденсатора - Мартинюк, В.В. (Технічна електродинаміка, 2011)
The frequency dependence of the equivalent nonlinear frequency dependent active resistance and the equivalent nonlinear frequency dependent capacitance is investigated from the input influence at its different working voltages. The analytical expression was obtained which allows to find the values of the electrochemical capacitor parameters at the different frequencies and voltages its charge. The diagram is given that represents the experimental values approximation results of the nonlinear impedance by means of the development nonlinear mathematical model of the electrochemical capacitor.